2022
DOI: 10.1109/lcomm.2022.3203984
|View full text |Cite
|
Sign up to set email alerts
|

One-to-Many Semantic Communication Systems: Design, Implementation, Performance Evaluation

Abstract: Semantic communication in the 6G era has been deemed a promising communication paradigm to break through the bottleneck of traditional communications. However, its applications for the multi-user scenario, especially the broadcasting case, remain under-explored. To effectively exploit the benefits enabled by semantic communication, in this paper, we propose a one-to-many semantic communication system. Specifically, we propose a deep neural network (DNN) enabled semantic communication system called MR DeepSC. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…is observed that the performance and stability of all the semantic communication systems at low SNR are significantly better than those of the traditional communication systems. Moreover, it is clear that our proposed multi-user cognitive semantic communication achieve better performance than MR-DeepSC [33]. The reasons are as follows.…”
Section: Rxmentioning
confidence: 95%
See 2 more Smart Citations
“…is observed that the performance and stability of all the semantic communication systems at low SNR are significantly better than those of the traditional communication systems. Moreover, it is clear that our proposed multi-user cognitive semantic communication achieve better performance than MR-DeepSC [33]. The reasons are as follows.…”
Section: Rxmentioning
confidence: 95%
“…Specifically, the DNN-based approaches, such as the joint source-channel coding (JSCC) approach [32] and the DeepSC approach [11], are compared with our proposed single-user cognitive semantic communication system. Besides, our proposed multi-user cognitive semantic communication system is compared with the MR-DeepSC approach [33]. Our proposed systems and other DNN-based benchmark systems are presented in Table VII.…”
Section: Performance Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the aforementioned wireless SemCom techniques, the rapidly evolving state-of-the-art research landscape of SemCom also encompasses numerous SemCom techniques and trends such as cognitive SemCom [122]; implicit SemCom [123]; adaptive SemCom [124]; contextbased SemCom [99], [125]; digital SemCom [126], [127]; SemCom with conceptual spaces [128]; inverse SemCom [129]; one-to-many SemCom [130]; cooperative SemCom [131]; strategic SemCom [132]; and encrypted SemCom [133]. These wireless SemCom techniques have also been corroborated to outperform traditional wireless communication techniques in low SNR regimes.…”
Section: A Wireless Semcommentioning
confidence: 99%
“…Based on the findings of [19], an approximation of the semantic similarity curve was studied in [21] along with the utilization of DeepSC for NOMA-based systems, while in [22] a quality of experience (QoE) maximization problem was analyzed. Moreover, in [23], the design and use of a DeepSC-like DNN were examined for serving two users. In this case, the training loss function was modified to take into account both users.…”
Section: A Literature Reviewmentioning
confidence: 99%